2012
DOI: 10.1002/hbm.22052
|View full text |Cite
|
Sign up to set email alerts
|

A crucial role for the cortico-striato-cortical loop in the pathogenesis of stroke-related neurogenic stuttering

Abstract: Neurogenic stuttering is an acquired speech disorder characterized by the occurrence of stuttering-like dysfluencies following brain damage. Because the onset of stuttering in these patients is associated with brain lesions, this condition provides a unique opportunity to study the neural processes underlying speech dysfluencies. Lesion localizations of 20 stroke subjects with neurogenic stuttering and 17 control subjects were compared using voxel-based lesion symptom mapping. The results showed nine left-hemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 52 publications
0
32
0
1
Order By: Relevance
“…However, all these studies concern developmental stuttering. Although neurogenic and developmental stuttering are suggested to share common neural substrates (Theys et al, 2012), its translation in CNV amplitude seems to be different. The neural network involved in fluent (and stuttered) speech is suggested to be differently interrupted causing the opposite observation in MH.…”
Section: Cnv Amplitude Related To Motor Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, all these studies concern developmental stuttering. Although neurogenic and developmental stuttering are suggested to share common neural substrates (Theys et al, 2012), its translation in CNV amplitude seems to be different. The neural network involved in fluent (and stuttered) speech is suggested to be differently interrupted causing the opposite observation in MH.…”
Section: Cnv Amplitude Related To Motor Preparationmentioning
confidence: 99%
“…Many of these areas are also assumed to be involved in developmental stuttering (e.g. Chang et al, 2009; originally thought to be two different entities, it now seems that both types of stuttering may share common neural characteristics (Theys et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This group of nuclei, which takes part in speech production (Crosson, 1992; Gracco & Abbs, 1987; Guenther, 2008), was first linked to stuttering indirectly: the association was made due to the BG’s interconnection with the supplementary motor area (SMA), which may also be involved in the disorder (Caruso, Abbs, & Gracco, 1988). Basal ganglia lesions are associated with the presence of acquired (neurogenic) stuttering following strokes (Theys et al, 2012) and traumatic brain injuries (Ludlow et al, 1987), and several case studies showed that such a scenario (acquired stuttering after a BG lesion) leads to speech disturbances similar to developmental stuttering in various behavioral and clinical dimensions (Heuer, Sataloff, Mandel, & Travers, 1996; Koller, 1983; Krishnan & Tiwari, 2011; Tani & Sakai, 2011). The BG also have critical role in sequence skill learning, which is deficient in PWS (e.g., Smits-Bandstra & De Nil, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Though the mechanism remains unclear, stuttering has been attributed to lesions in the supplementary motor area, pons, putamen, the left and right parietal lobes, the thalamus and the corpus callosum 18–21. Using voxel-based lesion-symptom correlates, Theys et al 22 showed that acquired stuttering from infarcts is not due to one specific lesion but rather a dysfunction in the left-sided neural network compromised of the cortex-basal ganglia-cortex.…”
Section: Introductionmentioning
confidence: 99%